PENGARUH PENERAPAN MODEL PEMBELAJARAN ARIAS DISERTAI TUGAS AWAL TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI IPA SMAN 8 PADANG (Universitas PGRI Sumatera Barat, 2011)
The problems in this research is the students Physic learning result is low. It is caused byinappropriate in choosing the learning models, so the students have low motivation. In thisresearch is used the ARIAS (Assurance, Relevance, Interest, Assessment, and Satisfaction)learning models with the starting assignments. The purpose of this research is to know the impactof the ARIAS learning models with starting assignment to the result of the students test at classXI IPA SMAN 8 Padang.This research is Experimental research. The population in this research is the students ofclass XI IPA SMAN 8 Padang. The data was taken through cluster random sampling, and theclass was chosen is class XI IPA 2 as experimental class, and XI IPA 1 as the class control. Thecognitive scoring is gotten through instrument test, and the affective scoring from observation.The hypothesis test used t – test.In the cognitive section, mean of the experimental class is 70, and the control class is 58,2. T – Test got th = 4, 74 and tt = 2,02, so the hypothesis is received. In the affective, the studentswho got the best criteria in the experimental class are 26 students. So, there is relationshipbetween the using of ARIAS learning models with starting assignments to the students physiclearning at XI IPA SMAN 8 Padang.